2015
DOI: 10.5296/gjes.v1i2.9261
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Global Educators? Their Significance in the Present Time and Implication for Quality Education

Abstract: Today, more than ever, globalisation is more evident and its effects are experienced by many people and many countries. This is apparent from the assumption that the future will be marked with complexity and a multitude of challenges. This is true even in the context of education. This is basically the reason on the needs for global educators who can be significantly helpful in shaping the future by establishing a learning environment which can help to increase the competencies of the students and to make them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…However, classroom teachers, faced with ever-increasing classroom size are not equipped to provide individualized curriculum at many different levels simultaneously (Osborn, 1996). Henceforth, in order to achieved inclusive global education, these issues must be given the kind of attention they deserve (Salihu & Ramadneh, 2015).…”
Section: ) Need For Challenging Educationmentioning
confidence: 99%
“…However, classroom teachers, faced with ever-increasing classroom size are not equipped to provide individualized curriculum at many different levels simultaneously (Osborn, 1996). Henceforth, in order to achieved inclusive global education, these issues must be given the kind of attention they deserve (Salihu & Ramadneh, 2015).…”
Section: ) Need For Challenging Educationmentioning
confidence: 99%
“…Findings revealed that the growth of youth population can lead to increased demands in higher education enrolment and learning. It was also found that the expansion of higher education in Southeast Asia led to the enhancements of their higher education systems that contributed to attracting more international students, thereby contributing to the youth population growth as well preparing youth to access quality education for shaping the future of society (Salihu & Ramadneh, 2015). This paper argues that the rapid growth of youth population in Southeast Asia contributes to the increasing trends in university enrolment in the region.…”
Section: Conclusion and Recommendationsmentioning
confidence: 88%
“…Although there is evidence of significant integration of digital technologies in education Salihu, & Ramadneh, [10] yet they are still regarded as optional in many cases. Better articulation of how digital technologies improved learning outcomes is required.…”
Section: Improved Learning Outcomes From High Quality Learning Enviro...mentioning
confidence: 99%